STRATEGI KOMUNIKASI PENGUATAN PERAN ADAT DALAM MENJAGA LINGKUNGAN BERLANDASKAN FALSAFAH TRI HITA KARANA DI DESA BATUAN KECAMATAN SUKAWATI KABUPATEN GIANYAR BALI - Hendrawathy Putri, I Dewa Ayu (Institut Hindu Dharma Denpasar, 2018)
Moral and religious values and ethics often provide valuable clues to the protection and preservation of the environment. The communication strategy undertaken by indigenous leaders as a design made to change human behavior on a larger scale through the transfer of new ideas in maintaining the environment based on the philosophy of Tri Hita Karana. Environmental problems are not solved only by scientific technology and methods but also need to be assisted by other forces of religion, beliefs, and ethics of the influence of human attitudes towards nature. Humans as individual and social beings take everything from their environment in an effort to meet their needs. Humans as God's most perfect creatures sometimes feel the most right to master and exploit nature beyond the limits of his needs. This led to a global crisis. This research uses descriptive qualitative method, which is a contextual research that makes man as an instrument and adapted to a reasonable situation in relation to data collection which in general is qualitative. Indigenous peoples of Bali live very dependent on the environment, they live, take care and utilize the environment since the first, even the traditional rituals performed as an expression and form of Praise and Prayer to the Creator is called the Tumpek Bubuh Ceremony. Moral and religious values and ethics often provide valuable clues to the protection and preservation of the environment.